Professional Development of Teachers in Public Secondary Schools: A Documentary Analysis - Domanog, Marbie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the professional development of secondary school teachers in the Dupax Del Sur District through a documentary analysis of the Results-Based Performance Management System (RPMS) for School Year 2023–2024. Anchored on the Human Capital Theory and the RPMS-IPCRF framework, the study aimed to identify teachers planned professional development activities, determine the professional development programs they participated in, analyze the alignment and misalignment of implemented activities with the IPCRF competency domains, and develop a professional development action plan based on identified needs. The study employed a qualitative research design using document analysis of 67 Individual Performance Commitment and Review Forms (IPCRFs) from Carolotan National High School, Dupax del Sur National High School, and Ganao National High School, supplemented by researcher-made interview questions for validation. Thematic analysis was used to identify patterns, categories, and gaps in teachers’ professional development experiences. Findings revealed that teachers planned and participated in various professional development activities related to content knowledge and pedagogy, learning environment, diversity of learners, curriculum and planning, assessment and reporting, community linkages and professional engagement, and personal growth and professional development. Most activities were aligned with IPCRF competency domains, demonstrating teachers’ commitment to improving instructional practices, learner support, and professional competencies. However, gaps were identified due to unimplemented planned activities, limited access to professional development opportunities, and some activities that were not fully aligned with targeted competencies. The study concluded that a contextualized, competency-based, and strategically aligned professional development system is necessary to strengthen teacher effectiveness. A School-Based Professional Development Action Plan was proposed to address identified gaps and support continuous professional growth. The study contributes to Sustainable Development Goal 4 (Quality Education) by strengthening teacher capacity and promoting improved educational practices. Its sustainability impact is reflected in the enhancement of institutional professional development systems through evidence-based planning, collaboration, and responsive capacity-building initiatives.